A Global Database of Domestic and International Tourist Numbers at National and Subnational Level - Richard S.J. Tol; Andrea Bigano; Jacqueline M. Hamilton; Yuan Zhou (Fondazione Eni Enrico Mattei (FEEM), 2005)
We present a new, global data base on tourist destinations. The data base differs from other data bases in that it includes both domestic and international tourists; and it contains data, for the most important destinations, data at national level as well as at lower administrative levels. Missing observations are interpolated using statistical models. The data are freely accessible on the internet.
Keywords: L83; 330; Tourism; Data; Tourismus; Internationaler Tourismus; Statistik; Statistische Daten; Welt